Nitrate Pollution and Fecal Coliform Contamination in Domestic Wells in the Vavuniya District Sri Lanka with Special Reference to Hospital Area - Loganathan*, P. (Recent Research in Science and Technology, 2011)
Ground water is generally polluted by leachates from sewage and agricultural lands. The main pollutants from sewages are nitrate nitrogen and fecal coliform. Both are hazardous when its level at high concentration in drinking water. The objectives of the study were to evaluate the nitrate nitrogen and fecal coliform count in wells and identify the wells that are not suitable for drinking purpose in Vavuniya District, Sri Lanka. Thirty three dug wells and three tube wells were selected around the general hospital Vavuniya to measure the Nitrate Nitrogen (N03-N), and fecal coliform count from March 2008 to February 2009. Mean NO3- N ranged from 0.40 to 16.2 mg/l over a twelve months period and 30.5 % of the wells were above the permissible limit of 10mg/l (well No11,12,13, 17,18,20,21,23, 25, 29 & 33) and these wells are not suitable for drinking purpose in almost all the months. Nitrate nitrogen in wet season was significantly higher than dry season (p= 0.072). The depth of wells varied from 4m to 8m and most of these wells were shallow wells. Shallow wells are very vulnerability to nitrate pollution in permeable soil. Almost all the wells were contaminated with fecal coliform. Wells closer to sand beds were contaminated with very high amount (more than 500) of fecal coliform. Improper sewage disposal system could be the reason for high nitrate nitrogen and fecal coliform contamination in wells around the hospital area.